Aortic Calcification and Arterial Stiffness Burden in a Chronic Kidney Disease Cohort with High Cardiovascular Risk: Baseline Characteristics of the Impact of Phosphate Reduction On Vascular End-Points in Chronic Kidney Disease Trial - Lioufas, Nicole M; Pedagogos, Eugenia; Hawley, Carmel M; Pascoe, Elaine M; Elder, Grahame J; Badve, Sunil V; Valks, Andrea; Toussaint, Nigel D (American journal of nephrology, 2020)
Chronic kidney disease (CKD) is associated with excess cardiovascular morbidity and mortality compared to the general population. Hyperphosphataemia, associated with vascular calcification and arterial stiffness, may play a key role in the pathogenesis of cardiovascular disease (CVD) associated with CKD, although phosphate reduction strategies have not consistently proven to beneficially affect clinically relevant outcomes. The IMpact of Phosphate Reduction On Vascular End-points in CKD (IMPROVE-CKD) study is an international, multi-centre, randomized, placebo-controlled trial investigating the effect of the phosphate binder lanthanum carbonate on intermediate cardiovascular markers in patients with stage 3b-4 CKD. The primary end-point is change in carotid-femoral pulse wave velocity (PWV, SphygmoCor) after 96 weeks. Secondary outcomes include change in abdominal aortic calcification (AAC, computed tomography), serum phosphate and fibroblast growth factor 23 (FGF-23). In total, 278 participants were recruited and randomized, mean age 63 ± 13 years, 69% male, 45% diabetes, 32% CVD, 33% stage 3b CKD and 67% stage 4 CKD. Mean estimated glomerular filtration rate and serum phosphate were 26.6 ± 8.3 mL/min/1.72 m2 and 1.25 ± 0.20 mmol/L, respectively. Median (interquartile range) intact and c-terminal FGF-23 levels were 133.0 (89.1-202) pg/mL and 221.1 (154.3-334.1) RU/mL, respectively. Mean PWV was 10.8 ± 3.6 m/s and 81% had AAC (median Agatston score 1,535 [63-5,744] Hounsfield units). PWV ≥10 m/s was associated with older age, diabetes, CVD, presence of AAC, higher systolic blood pressure (BP), larger waist circumference and higher alkaline phosphatase. AAC was associated with older age, male sex, diabetes, CVD, higher diastolic BP, dyslipidaemia (and use of statins), smoking, larger waist circumference and increased PWV. In conclusion, IMPROVE-CKD participants had high baseline risk for cardiovascular events, as suggested by high baseline PWV and AAC values.